Post-Priestly additions and rewritings in Exodus 35-40: an analysis of MT, LXX, and Vetus Latina - Lo Sardo, Domenico (Forschungen zum Alten Testament / 2, 2020)
Cover -- Title -- Acknowledgements -- Table of Contents -- List of Tables -- Abbreviations -- Chapter 1: Introduction -- 1.1 Preamble -- 1.2 Identification of the Textual and Literary Problem -- 1.3 Previous Problem in Exod 25-31 and 35-40 -- 1.4 Working Hypothesis of the Monograph -- 1.5 Working Methodology: Text and Literary Critical Method -- Chapter 2: History of Research from Origen to the Qumran Discoveries -- 2.1 Preamble -- 2.2 The Origins -- 2.3 Change of Direction -- 2.4 The Most Significant Stages of the Question -- 2.5 The Most Recent Studies -- 2.6 Qumran -- 2.7 Summary and Assessment -- Chapter 3: The Construction of the Sanctuary: Text-Critical Study of Omissions and Additions in Exod 35-40 -- 3.1 Preamble -- 3.2 Text-Critical Study of MT Exod 36:8b-34 (LXX Exod 37:1-2) -- 3.2.1 Description of the Variant -- 3.2.2 Quantitative and Qualitative Differences between LXX-MT Exod 26:1-29 and MT-Orh Exod 36:8aß-34 -- 3.2.2.1 Differences in the Vorlage -- 3.2.2.2 The Dependence of the Hexaplaric Text from LXX Exod 26 in Comparison with MT -- 3.2.2.3 Identification of Different Authors for the Two Sections (Exod 26// MT Exod 36:8aß-34) -- 3.2.2.4 Variations in Spelling -- 3.2.3 A Further Observation -- 3.2.4 Toward a Conclusion -- 3.3 Text-Critical Study of LXX Exod 38:18-20 (Absent in MT) -- 3.3.1 Description of the Variant -- 3.3.2 Exod 38 in LXX, MT, and VL -- 3.3.3 Exod 38:18-20: Addition, Omission, or a Different Vorlage? -- 3.3.3.1 A Further Observation -- 3.3.3.2 A Possible Solution -- 3.3.3.3 Toward a Conclusion -- 3.4 Text-Critical Study of Exod 37:17-24 (LXX 38:13-17) -- 3.4.1 Description of the Variant -- 3.4.2 A First Observation on MT-SP-LXX Exod 25:38-39 -- 3.4.3 Exod 37 in LXX, MT, and VL -- 3.4.3.1 A Further Observation -- 3.4.3.2 A Possible Solution -- 3.4.3.2.1 Intertextual Comparison -- 3.4.3.2.2. Extrabiblical Data.